2017
DOI: 10.2174/0929867324666170203122625
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ion Channels, Cellular Carriers and Na(+)/K(+)/ATPase by Janus Kinase 3

Abstract: Janus kinase-3 (JAK3), a tyrosine kinase, is expressed in a variety of tissues, including the brain and is involved in the signaling of cytokine receptors. JAK3 participates in numerous functions, such as cell survival and proliferation, neuroprotection, apoptosis and the cellular response to hypoxia and ischemia-reperfusion. This kinase further contributes to the signaling of hematopoietic cell cytokine receptors, activation of dendritic cells, maturation, and immune suppression as well as to cell volume regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, under the condition of ischemia and hypoxia, the intracellular adenosine triphosphates are depleted soon, which decreases the function of sodium-potassium pump, resulting in the accumulation of intracellular Na + ions and causing edema and functional decline of cells and organelles. 20 , 21 The lack of oxygen damages the mitochondrial respiratory chain and produces a large number of oxygen-free radicals, causing severe ischemia-reperfusion injury after blood reperfusion. 22 With the increase of ischemia time, the preservation effect gradually deteriorates, affecting the success rate of replantation and long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, under the condition of ischemia and hypoxia, the intracellular adenosine triphosphates are depleted soon, which decreases the function of sodium-potassium pump, resulting in the accumulation of intracellular Na + ions and causing edema and functional decline of cells and organelles. 20 , 21 The lack of oxygen damages the mitochondrial respiratory chain and produces a large number of oxygen-free radicals, causing severe ischemia-reperfusion injury after blood reperfusion. 22 With the increase of ischemia time, the preservation effect gradually deteriorates, affecting the success rate of replantation and long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of JAK3 significantly increased Na + /K + -ATPase (Hosseinzadehet al, 2015). Recent studies found that JAK3 directly affected the transport proteins in partial, including various ion channels, a number of cellular carriers and the Na + /K + pump including the high-affinity Na + coupled glucose transporter SGLT1, the excitatory amino acid transporters EAAT1, EAAT2, EAAT3 and EAAT4, the peptide transporters PepT1 and PepT2, CreaT1 and the Na + /K + -ATPase (Sopjani, Thaci, Krasniqi, Selmonaj, Rinnerthaler & Dermaku-Sopjani, 2017). There need additional experiments to elucidate the mechanisms and prerequisites of up-or down-regulation of Na + /K + -ATPase by JAK3 or JAK2.…”
Section: Jak-stat In Epithelial Function/ Smooth Muscle Proliferation...mentioning
confidence: 99%
“…The attachment of the virus to the host cell membrane during infection is mediated by the S protein and ACE2 proteins, respectively, which determine the host range (Figure 1). The human cell membrane contains numerous protein and lipid molecules (Sopjani et al, 2015, 2016, 2017, 2019, 2021, Sopjani & Dërmaku‐Sopjani, 2016, Dërmaku‐Sopjani & Sopjani, 2019), each of which conducts or participates in specific cellular processes. ACE2 is one of the transmembrane plasma membrane proteins (Dërmaku‐Sopjani & Sopjani, 2021b).…”
Section: Introductionmentioning
confidence: 99%